Etoricoxib–NLC Mitigates Radiation-Induced Ovarian Damage in Rats: Insights into Pro-Inflammatory Cytokines, Antioxidant Activity, and Hormonal Responses - Sahar Khateeb (Biomolecules)
Radiotherapy is a critical treatment for cancer but poses significant risks to ovarian tissue, particularly in young females, leading to premature ovarian failure (POF). This study examines the therapeutic potential of etoricoxib nanostructured lipid carriers (ETO-NLC) in mitigating radiation-induced ovarian damage in female Wistar rats. Twenty-four female rats were randomly assigned to four groups: a control group receiving normal saline, a group exposed to a single dose of whole-body gamma radiation (6 Gy), a group treated with etoricoxib (10 mg/kg) post-radiation, and a group treated with ETO-NLC for 14 days following radiation. Histopathological evaluations and oxidative stress biomarker assessments were conducted, including ELISAs for reactive oxygen species (ROS), pro-inflammatory cytokines (IL-1β, TNF-α), and signaling molecules (PI3K, AKT, P38MAPK, AMH). Serum levels of estrogen, FSH, and LH were measured, and gene expression analysis for TGF-β and Nrf2 was performed using qRT-PCR. The findings indicate that ETO-NLC has the potential to ameliorate the harmful effects of ovarian damage induced by γ-radiation. These therapeutic effects were achieved through the modulation of oxidative stress, inflammation, augmentation of antioxidant defenses (including Nrf2 activation), support for cell survival pathways (via PI3K/Akt signaling), regulation of MAPK, mitigation of fibrosis (TGF-β), and preservation of ovarian reserve (as evidenced by AMH, FSH/LH, and estrogen levels). ETO-NLC shows promise as an effective strategy for attenuating radiation-induced ovarian damage, highlighting the need for further research to enhance therapeutic interventions aimed at preserving ovarian function during cancer treatment.